A new species of highland loach, Schistura sirindhornae, from the upper Chao Phraya River basin, Thailand (Pisces: Ostariophysi: Nemacheilidae) - Suvarnaraksha, Apinun (Zootaxa, 2015)
Schistura sirindhornae, a new species of nemacheilid, is described from the Nan River basin in northern Thailand. It is distinguished from all other species of Schistura in having overlapping scales on the entire body similar to scales of balitorids, transparent scales on the belly and thorax, a lateral-line canal that is similar to that of most cyprinids and balitorids in being present across the entire lateral-line surface of the scale instead of being represented only by a pore. It also has a unique color pattern of irregular brown bars on the back and side of the faint yellow-orange body, a bright triangular orange mark on the occiput, an orange crown-shaped mark between the eyes, an uninterrupted black mark along the base of the dorsal fin, a crescent-shaped bar on the base of the caudal fin, and bright iridescent orange areas on the upper and lower extremities of the caudal-fin base. Schistura sirindhornae is known only from the upper Nan River drainage, Nan Province, Thailand.